2000
DOI: 10.1063/1.373591
|View full text |Cite
|
Sign up to set email alerts
|

Interparticle interactions in magnetic recording media as obtained from high-order measurements by a Preisach model

Abstract: Generalized ΔM plots, which allow interactions to be investigated for any starting remanence state, have been used in the analysis of interactions in particulate magnetic recording media for three samples [very high speed (VHS) videotape, Ba-ferrite dispersed particles oriented and nonoriented]. The results have been interpreted using a generalized moving Preisach model. This gives a good fit to the hysteresis loops and ΔM plots. However, agreement with the generalized ΔM plots is less complete. This is interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…(1) for major loops [b(H C ) is given by Eq. (2) [35,63,64]. However, we have found that the MPM alone is not able to describe properly the hysteresis cycles of our multilayers with PMA, and a nonlinear dependence ofH B with m is necessary.…”
Section: Distribution Of Interactionsmentioning
confidence: 84%
See 2 more Smart Citations
“…(1) for major loops [b(H C ) is given by Eq. (2) [35,63,64]. However, we have found that the MPM alone is not able to describe properly the hysteresis cycles of our multilayers with PMA, and a nonlinear dependence ofH B with m is necessary.…”
Section: Distribution Of Interactionsmentioning
confidence: 84%
“…A detailed explanation regarding the selection of b(H C ) which accounts for the history of the system and allows for the calculation of minor hysteresis loops can be found in [34]. The Preisach distribution p(H C ,H B ) represents all the microstructural and magnetic features affecting the magnetization reversal process [34,35]. We assume that H C and H B are statistically independent, and thus the Preisach distribution p(H C ,H B ) is written as the product of the distribution of coercive fields f (H C ) and the distribution of interaction fields g(H B ), as given by…”
Section: Preisach Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the initial demagnetization process in the IRM process is an important source of errors in the interpretation of the deltaM curves and this was the main reason to introduce generalized deltaM curves and the IGDM curve. 8,9 In the CPM, FORCs and SORCs can be expressed using the Everett integral, which is given by and one can observe that the second-order derivative ͑1͒ applied to these expressions gives the same result, the Preisach distribution:…”
mentioning
confidence: 98%
“…This will allow a comparison of the results obtained with the FORC diagram method with other experimental methods, such as the well-known deltaM 6,7 and generalized deltaM procedures. 8 These methods have long been used and are still used for the evaluation of the intensity of interactions in magnetic systems.…”
mentioning
confidence: 99%